PEMBANGUNAN PENEGAKAN HUKUM PIDANA YANG MENGEFEKTIFKAN KORPORASI SEBAGAI SUBJEK TINDAK PIDANA KORUPSI - Siswanto, Heni (Lampung University, 2015)
The criminal law enforcement policy (PHP), currently associated, corporations as subjectâs perpetrators of corruption (TPK) include PHP in the formulation stage, the application stage and the execution stage. PHP formulation stage (in abstracto) is based on Article 20 of Law on Corruption which should be a strong legal basis to hold corporations as subjects of TPK, TPK equivalent to the subject of TPK doers of civil servants and individuals. PHP application stage (in concreto) indicates that the corporation as the subject TPK doers very rarely applied / applied to account for the corporation as a principal TPK arguing that criminal sanctions can be imposed is limited; the difficulty of proving corporation fault; the difficulty of law enforcement officers discovered the theory / doctrine and legal basis of corporate errors. Development of PHP policy streamlineÂ Â corporation as the subject doers of TPK in the future related to the renewal of substance, structure and legal culture of corruption and streamline the corporation as a subject the perpetrator TPK. Renewal terms of substance related to the formulation of criminal crime, fault / criminal liability as well as criminal and punishment (strafsoort, strafmat and strafmodus / modaliteit); Renewal in terms of the legal structure of corruption related to the need for law enforcement agencies that further enhance the insight to streamline the corporation as a subject TPK; the need to retain the presence of the Corruption Eradication Commission (KPK); corporate case handling is done by a special team; maximizing the expert testimony; maintain the Police Commission, the Prosecutorial Commission and the Judicial Commission of the role to supervise the conduct of law enforcement. Renewal in terms of legal culture of corruption, which need to be considered more attention to the educational curriculum of character education (mental reform); understanding to the public that corporations as well as TPK subject that needs to be optimized in PHP; anticipation of an attempt to thwart PHP with the corporation as TPK subject to foul play; the issue of jurisdiction, both to those who do and those who receive bribes / gratuities, because they both do TPK.Â Keywords: Development, The criminal law enforcement Policies, Corporations, Subjectâs Perpetrators of Corruption.